Arabic language in multicultural dynamism: chronological effects on Nigeria’s heritage (2014)
Of such notice that researchers documented in their compendium about the spawn of Arabs and their language dwindled in mono-culture boundary for many memorable years. It is of the fact that the relevance of Arabic language is not only restricted to the people spoken it as their mother language. Thus, it is globally applauded due to its effective recognitions and relevancies in other cultures and all human strata. History show that the place of Arabic language in multicultural society is very applausive, especially after the emergence of Islam spread beyond its domain to other continents like Asia, Europe, Africa, America, etc. Apparently, the position of Arab language in multicultural societies especially Nigeria (has the largest African population) which has predominant ethnic groups, cultures, and are than 400 ethnic dialects, with over 1.850,000,000 population is given a warmly applausive recognization. The reason is that its entry into the country dated back to the seventh century of the Hjrah era in which Arabic had been used for religious, social, economic, and cultural purposes. Therefore, this paper is aiming to give an expository analysis of the relevance of Arabic language in multicultural society and take Nigeria as a case study.